Partial intestinal Atresia (Stenosis) in a day-old Beetal goat kid: A case report (Indian Journal of Veterinary Pathology, 2026)
A one-day-old male goat kid was presented for necropsy with clinical signs of abdominal distension, weakness, and absence of faecal passage since birth. Gross examination revealed a segmental narrowing of the ileum approximately 15–20 cm proximal to the ileocecal junction. The affected part had a markedly reduced lumen diameter, resulting in partial obstruction. The proximal small intestine was severely dilated, haemorrhagic and filled with blood-tinged fluid, while the distal intestine was collapsed and empty with reduced lumen size. Histopathology of distal part showed reduced lumen diameter with intact intestinal wall layers, reduced villi and mild mucosal congestion while the proximal dilated segments showed mucosal flattening, loss of villi, congestion and marked submucosal haemorrhage. The condition was diagnosed as partial intestinal atresia (stenosis), a rare congenital anomaly in goat kids.